Advanced Breast Cancer at Diagnosis: Over One Third Adherent to Screening Recommendations - Orli Friedman-Eldar; Douglas Zippel; Helit Guy-Chen; Shlomi Eitan Gur; Noa Ben-Baruch; Eran Sharon; Tanir M. Allweis (Mary Ann Liebert, 2020)
Background: Advanced breast cancer (ABC) at diagnosis carries a worse prognosis, and can be attributed to delay in diagnosis, failure of screening tests, or aggressive biology. Better understanding of factors related with ABC at diagnosis could help decrease the proportion of such cases. Patients and Methods: This is a retrospective study of all patients diagnosed and treated for breast cancer (BC) at a single institution between 2012 and 2015. Data were collected from medical records and phone interviews, and included demographic, clinical, and tumor-related data, and adherence to screening recommendations. Results: Of 555 newly diagnosed BC patients, 390 (70.3%) were diagnosed early (stage 0?IIa), and 165 (29.7%) were diagnosed with ABC (stage IIb?IV). Of the165 patients diagnosed with ABC, 57 (34.5%) underwent screening mammography as recommended. More patients with ABC were <50 years (29.1% vs. 19%, p?=?0.006). ABC was associated with higher grade, higher proliferation rate, Her2/neu overexpression, luminal B-like, and triple negative phenotypes. Mammography within 30 months of diagnosis was more prevalent among those diagnosed early (64.6% vs. 34.5%, p?=?0.003). Only 31 (18.8%) of the screening eligible patients who were diagnosed at advanced stage did not adhere to screening recommendations. Conclusions: ABC at diagnosis is related to aggressive tumor biology and age <50 years. It is also associated with lower adherence to screening mammography; however, more than one third of patients diagnosed with ABC who were eligible for screening underwent screening mammography as recommended. Further research is needed to elucidate factors related with ABC at diagnosis, review screening guidelines, and develop more effective screening modalities.